Simple Equations for Considering Spatial Variability on the Bearing Capacity of Clay - Davood Azan; Abdolhossein Haddad (Salehan Institute of Higher Education, 2019)
In the present paper, the effect of spatial variability of undrained shear strength on the bearing capacity of shallow strip footing on clay was investigated and two new and simple equations were introduced for incorporating the effect of soil variability parameters on the undrained bearing capacity of strip footing on clay. For investigating the spatial variability of clay, undrained shear strength was assumed as a spatial variable parameter with the use of random field theory. The Monte Carlo simulation technique was used to obtain the probability distribution of the bearing capacity of footing on nonhomogeneous clay. The spatial variability of the undrained shear strength was investigated using three controlling parameters: coefficient of variation (COV) of the undrained shear strength as well as the scales of fluctuation of the shear strength in horizontal and vertical directions. The Mohr-Coulomb failure criterion and finite difference method were used to model the plastic behaviour of soil and calculate the bearing capacity of the footing. The results show that by increasing the COV of the undrained shear strength, the average bearing capacity decreases while the COV of the bearing capacity increases. Moreover, the average bearing capacity of footing has an approximate increasing trend with increasing the scales of fluctuation.